The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fnins.2020.00362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Auditory Predictability on the Human Peripheral Auditory System

Abstract: Auditory perception is facilitated by prior knowledge about the statistics of the acoustic environment. Predictions about upcoming auditory stimuli are processed at various stages along the human auditory pathway, including the cortex and midbrain. Whether such auditory predictions are processed also at hierarchically lower stages-in the peripheral auditory system-is unclear. To address this question, we assessed outer hair cell (OHC) activity in response to isochronous tone sequences and varied the predictabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 82 publications
0
4
1
Order By: Relevance
“…The present results might be more closely related to a study by Dragicevic et al [ 17 ] who showed some correlations in the modulation of OAEs and ERPs, although these were of a different kind than in the present study. There are also the interesting results by Riecke et al [ 41 ] who showed some relationship between OAEs and the N1, although our work failed to detect such a connection.…”
Section: Discussioncontrasting
confidence: 64%
“…The present results might be more closely related to a study by Dragicevic et al [ 17 ] who showed some correlations in the modulation of OAEs and ERPs, although these were of a different kind than in the present study. There are also the interesting results by Riecke et al [ 41 ] who showed some relationship between OAEs and the N1, although our work failed to detect such a connection.…”
Section: Discussioncontrasting
confidence: 64%
“…In contrast, Dragicevic et al [20] reported significant correlations between the oscillatory DPOAE signal and cortical oscillations at low frequencies (< 10 Hz) mainly when attention was switched from the visual to the auditory modality. Finally, studying predictive processing using an intermodal predictability paradigm Riecke et al [45] found a relationship between DPOAE and brain effects. However, this relationship is limited to participants that benefited from predictions.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these animal studies, Riecke et al. (2020 ) found that the predictability of the frequency of upcoming tones alters OAE amplitude in a fashion that depends on the behavioral relevance of the tone sequences ( Riecke et al. 2020 ).…”
Section: Discussionmentioning
confidence: 76%